Curative care expenditure of outpatient anxiety disorder in Liaoning Province, 2015-2020-based on “System of Health Accounts 2011” - Xx, S; Zhao, Yue; Wan, Quan; Chai, Peipei; Ma, Yuedan (Frontiers in Public Health, 2024)
Introduction: Anxiety disorders are the most common mental disorder, experienced by more than a quarter of the population. This study examines total outpatient curative care expenditures (CCE) for anxiety disorders and changes in their composition based on the System of Health Accounts 2011 (SHA 2011).Methods: This study used multi-stage stratified random from a total of 93,18513 outpatient sample data by 920 healthcare organizations, a total of 109,703 cases of anxiety disorders from 53 sample organizations (5.76%) from 2015-2020. Univariate analysis, multifactor analysis and structural equation modeling (SEM) were used to explore the influential factors affecting outpatient CCE for anxiety disorders.Results: Anxiety disorder outpatient CCE from 2015-2020 continued to increase from CNY 99.39million in 2015 to CNY 233.84 million in 2020, mainly concentrated in western medicine costs, 15-64 years, general hospital, generalized anxiety disorder and public financing. The results of univariate analysis showed statistically significant differences in all subgroups, and the results of multivariate analysis and SEM showed that the choice to purchase western drugs, purchase prepared Chinese drugs, choice to have a checkup, urban employees' basic medical insurance, and 0-14 years old were associated with high anxiety disorder outpatient CCE.Initiatives to improve the essential drug system, reduce the out-of-pocket (OOP) ratio, and strengthen primary health care to effectively reduce the medical burden on patients.